Istisna' model for construction works' contract - Abdul Rashid, Khairuddin (2015)
Istisna’ has been accepted as the Shariah compliant tool for a transaction wherein the subject matter is yet to exist. In the case of construction works’ contracts the current Istisna’ practice appears to be skewed towards meeting the needs and requirements of the international funding institutions, hence the use of parallel Istisna’. However, the documentation aspects of Istisna’ contracts is seldom discussed. In this presentation, Istisna’ in general and its application and documentation for construction works’ contracts is critically examined. The outcome of the examination suggests that for construction works’ contracts direct Istisna’ is preferred. In addition, in effort to achieve validity of the Istisna’ contract a comprehensive set of documentation is required. It is proposed herein that the use of bills of quantities (BQs) would enable this requirement to be satisfied. Keywords: Building, Bills of Quantities (BQs), Construction, Contract, Istisna’, Quantity Surveying, Shari’ah